BILANGAN KROMATIK HARMONIS PADA GRAF PAYUNG, GRAF PARASUT, DAN GRAF SEMI PARASUT - Fransiskus Fran; Nilamsari Kusumastuti; Robiandi (Jurnal Matematika Sains dan Teknologi, 2023)
This article discusses the harmonic coloring of simple graphs G, namely umbrella graphs, parachute graphs, and semi-parachute graphs. A vertex coloring on a graph G is a harmonic coloring if each pair of colors (based on edges or pair of vertices) appears at most once. The chromatic number associated with the harmonic coloring of graph G is called the harmonic chromatic number denoted XH(G). In this article, the exact values ​​of harmonic chromatic numbers are obtained for umbrella graphs, parachute graphs, and semi-parachute graphs.